RANCANG BANGUN SISTEM KENDALI IRON REMOVAL FILTER (IRF) PADA UNIT PENGOLAHAN AIR BERSIH BERBASIS PLC - Karyadi, Kukuh; Suseno, Jatmiko Endro (BERKALA FISIKA, 2019)
Water is a necessity of life and is very important for everyone. The availability of clean water has been fulfilled in various ways. The Iron Removal Filter (IRF) control system is one processings and it is still used in the ordinary water treatment plant. However, it is still manually operated so that it need many the processings. The aim of this research is to develop the automatic IRF processing unit using the Programmable Logic Controller (PLC). The control system contained PLCs, relay circuits, power supplies and Human Machine Interfaces (HMIs) to control the clean water processing unit including controlling the IRF process automatically. The prototype of the water treatment plant consisted of an aerator unit, an IRF unit, a storage tank, several pumps, and some control valves were controlled by the operating control system. The control system could be easily operated and it has a very attractive appearance using HMI. Therefore, it is highly recommended to be used in the actual clean water treatment unit.Keywords: water treatment plant, Iron Removal Filter (IRF), PLC and HMI